TEVRAT VE KUR'AN'A GÖRE MISIR HALKININ BAŞINA GELEN ON BELA - AK, HARUN (Fırat Üniveristesi, 2024)
Mısır halkının başına gelen on bela konusu Tevrat ve Kur'an ekseninde işlenmiştir. Ayrıca bu belaların nasıl meydana geldiği ve nasıl bir süreç işlendiği vb. konulara açıklık getirilmiştir. Tevrat'taki ilgili pasajlar ve Kuran'daki ilgili ayetler taranmış on bela hakkında genel bir çerçeve oluşturulmuştur. Tevrat ve Kuran'a göre Mısır halkının başına gelen on bela ile ilgili yaptığımız bu çalışma giriş kısmı ile beraber beş başlıktan oluşmaktadır. Çalışmamızın giriş kısmında konunun önemi amacı ve metoduyla ilgili bilgiler verilmiş, bela ve bela ile ilgili kavramlar açıklanmıştır. İkinci başlıkta Tanrı'nın yeryüzüne gönderdiği belalar Tevrat ve Kur'an ekseninde incelenmiştir. Üçüncü başlıkta Mısır halkının başına gelen on bela Tevrat'ın bakış açısıyla sunulmuştur. Dördüncü başlıkta bu belalar Kur'an merkezli tahlil edilmiştir. Sonuç kısmında ise çalışmamıza konu olan Mısır halkının başına gelen on bela genel bir değerlendirmeye tabi tutulmuştur.

The ten plagues that befell the Egyptian people are covered on the axis of the Torah and the Qur'an. In addition, it has been clarified how these troubles occur and what kind of process is processed, etc. Relevant passages in the Torah and relevant verses in the Qur'an have been scanned, and a general framework has been established about the ten plagues. According to the Torah and the Qur'an, this study on the ten calamities that befell the Egyptian people consists of five headings with the introduction. In the introduction part of our study, information about the importance, purpose and method of the subject is given, and the concepts related to trouble and trouble are explained. In the second chapter, the plagues sent by God to the earth are examined on the axis of the Torah and the Qur'an. In the third chapter, the ten plagues that befell the Egyptian people are presented from the point of view of the Torah. In the fourth chapter, these troubles are analyzed in the Qur'an. In the conclusion part, ten troubles that befell the Egyptian people, which are the subject of our study, were subjected to a general evaluation.
According to the Torah and the Qur'an, the ten plagues that befell the Egyptian people
Keywords: Din